Anthropogenic modification of forests means only 40% of remaining forests have high ecosystem integrity - H. S. Grantham; A. Duncan; T. D. Evans; K. R. Jones; H. L. Beyer; R. Schuster; J. Walston; J. C. Ray; J. G. Robinson; M. Callow; T. Clements; H. M. Costa; et al. (Nature Communications, 2020)
Mapping and quantifying degree of forest modification is critical to conserve and manage forests. Here the authors propose a new quantitative metric for landscape integrity and apply it to a global forest map, showing that less than half of the world’s forest cover has high integrity, most of which is outside nationally designed protected areas.